An Integrated Bulk and Surface Modification Strategy for Gas‐Quenched Inverted Perovskite Solar Cells with Efficiencies Exceeding 22%. Issue 6 (17th March 2022) - Zhang, Xin; Qiu, Weiming; Song, Wenya; Hawash, Zafer; Wang, Yaxin; Pradhan, Bapi; Zhang, Yiyue; Naumenko, Denys; Amenitsch, Heinz; Moons, Ellen; Merckx, Tamara; Aguirre, Aranzazu; et al.
Abstract : Inverted perovskite solar cells (PSCs) prepared by the antisolvent method have achieved power conversion efficiencies (PCEs) of over 23%, but they are not ideal for device upscaling. In contrast, gas‐quenched PSCs offer great potential for upscaling, but their performance still lags behind. Herein, the gas‐quenched films through both surface and bulk modifications are upgraded. First, a novel surface modifier, benzylammonium thiocyanate, is found to allow remarkably improved surface properties, but the PCE gain is limited by the existence of longitudinally multiple grains. Thus, methylammonium chloride additive as a second modifier to realize monolithic grains is further utilized. Such an integrated strategy enables the average open‐circuit voltage of the gas‐quenched PSCs to increase from 1.08 to 1.15 V, leading to a champion PCE of 22.3%. Moreover, the unencapsulated device shows negligible degradation after 150 h of maximum power point operation under simulated 1 sun illumination in N2 . Abstract : A combined application of benzylammonium thiocyanate surface modification and methylammonium chloride additive engineering is applied to improve film quality of Cs–FA double‐cation perovskite, helping to achieve enlarged and monolithic perovskite grains, better interfacial properties, and passivate the nonradiative recombination centers. As a result, a distinguished power conversion efficiency of 22.3% is realized for gas‐quenched inverted p–i–n perovskite solar cells.